The relationship of holidays and perceived quality of life for university students - Tsou, Ming Ta (2017)
Abstract: The college segment market is an area that has not been fully explored throughout travel literature. Most research that investigates students’ travel behavior, however, put the majority of the emphasis on understanding different travel motivations such as the application of the push and pull theory, which is very commonly seen in tourism literature. This study aims to find out the factors that influence the way college students make travel decision as well as the factors influencing their level of satisfaction after vacationing. A total of 64 students currently studying in the University of Nottingham in the UK filled out an online survey and were data analyzed. Through using content analysis and Pearson’s coefficient of correlation as means of data analysis, the results show that college students are mostly driven by making memories, learning new and different things and reliving stress from school when it comes to traveling. Culture and heritage activities, nature-based activities and visiting cities and shopping are the most popular activities in this research. The overall results show that taking vacations have positive influences on the perceived quality of life of college students.